Position of Credit Agreement in the Provision of Credit Facilities at a Banking Institution - Sampurna, Asbit Iman (Sultan Agung Notary Law Review, 2024)
This study aims to determine the position of the credit agreement in the implementation of the provision of credit facilities at a banking institution, in addition to determining the legal consequences that will occur if the requirements of the credit agreement are not met. The method used in this study uses the normative legal approach method, namely an approach based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this study. This approach is also known as the literature approach method. The results of this study indicate that, first: the position of the credit agreement in the credit granting process is very important. Second: in order to provide legal protection for the parties, both creditors and debtors, the credit agreement must be implemented in accordance with applicable requirements.